Dual-Engineering Tailored Co3O4 Hollow Microspheres Assembled by Nanosheets for Boosting Oxygen Evolution Reaction - Yinghan Cui; Shiduo Yang; Jianqiang Zhu; Zaidong Wang; Sen Chen; Jian Qi; Huan Wang (Molecules)
The development of efficient, low-cost electrocatalysts for the oxygen evolution reaction (OER) is crucial for advancing sustainable hydrogen production through water splitting. This study presents a dual-engineering strategy to enhance the OER performance of Co3O4 by synthesizing hollow microspheres assembled from nanosheets (HMNs) with abundant oxygen vacancies and highly active crystal facet exposure. Through a modified one-step hydrothermal process, Co3O4 HMNs with exposed (111) and (100) crystal facets were successfully fabricated, demonstrating superior OER activity compared to Co3O4 nanocubes (NCs) with only (100) facet exposure. The optimized Co3O4-5% HMNs exhibited a low overpotential of 330 mV at 10 mA cm−2 and a Tafel slope of 69 mV dec−1. The enhanced performance was attributed to the synergistic effects of crystal facet engineering and defect engineering, which optimized the Co-O bond energy, increased the number of active sites, and improved conductivity. The unique hollow structure further facilitated mass transport and prevented nanosheet stacking, exposing more edge sites for catalytic reactions. This work highlights the potential of geometric and electronic structure modulation in designing high-performance OER catalysts for sustainable energy applications.